2002
DOI: 10.1016/s0378-1097(02)00815-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcript levels of rbcR1, ntcA, and rbcL/S genes in cyanobacterium Anabaena sp. PCC 7120 are downregulated in response to cold and osmotic stress

Abstract: Using differential display, we identified the Anabaena sp. PCC 7120 ribulose 1,5-bisphosphate carboxylase transcriptional regulator (rbcR1) gene, a member of the LysR family of positive transcription factors. The rbcR1 transcript and its putative target gene ribulose 1,5bisphosphate carboxylase/oxygenase (rbcL/S) were repressed by cold (20 ‡C) and osmotic (sucrose and salt) stress. Cold stress also induced a transient downregulation of the Anabaena 7120 ntcA transcriptional regulator. Expression of the ntcA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We also found that cmpR transcript is more abundant in Ci-limited cells in this strain. Additionally, the third cbbR homolog, rbcR, which is believed to encode a regulator of the rbcLS operon by virtue of the function of its proteobacterial homolog (Mori et al, 2002), was not transcriptionally induced by Ci limitation in this study.…”
Section: Early Transcriptional Response Of Synechococcus To Severe CImentioning
confidence: 52%
See 1 more Smart Citation
“…We also found that cmpR transcript is more abundant in Ci-limited cells in this strain. Additionally, the third cbbR homolog, rbcR, which is believed to encode a regulator of the rbcLS operon by virtue of the function of its proteobacterial homolog (Mori et al, 2002), was not transcriptionally induced by Ci limitation in this study.…”
Section: Early Transcriptional Response Of Synechococcus To Severe CImentioning
confidence: 52%
“…A family of three Lys-R-type transcriptional regulators, related to the CbbR regulators of Calvin cycle gene expression in proteobacteria, have been identified in Synechocystis (Figge et al, 2001). Of these, ndhR and cmpR encode transcriptional regulators of the ndhF3/D3/chpY (cupA) and cmp operons, respectively (Figge et al, 2001;Omata et al, 2001), whereas RbcR is thought to be involved in control of the rbc operon (Mori et al, 2002). Despite the rapid progress in defining the genetic basis of the cyanobacterial CCM, the first integrated study of the transcriptional response of CCM-related genes to Ci limitation was published only recently, from work in Synechocystis (McGinn et al, 2003).…”
mentioning
confidence: 99%
“…The downstream events in the Ci signaling pathway are better characterized, and LysR-type transcriptional factors are known to be involved in the regulation of high-affinity Ci-transporter gene expression. NdhR (CcmR) and CmpR regulate ndhF3/D3/chpY (cupA), and cmpABCD and sbtA expression, respectively, in Synechocystis PCC6803 (Figge et al, 2001;Omata et al, 2001;Wang et al, 2004), while RbcR is thought to be involved in control of the rbc operon (Mori et al, 2002). Only rbcR and cmpR have been identified in Synechococcus PCC7942.…”
Section: -Dependent Hcomentioning
confidence: 99%
“…Previous pharmacological studies suggested that PP2A might be involved in cold stress signaling [101]. Recently, PP2A was shown to play roles in ABA activation of slow anion channels in guard cells because the rcn1 mutant exhibited ABAinsensitivity to ABA in stomatal closure and was impaired in slow anion channels regulation by ABA [102].…”
Section: Protein Phosphatasesmentioning
confidence: 99%
“…Much work has been devoted to the effects of nitrogen sources but little study has been done on the effects of abiotic stresses. For instance, it was suggested that in response to abiotic stress such as cold stress and osmotic stress, Anabaena 7120 enhanced its nitrogen assimilation by inducing the expression of ntc A gene [101]. The effects of osmotic stress imposed by penetrating and non-penetrating solutes on the regulation of this gene at both transcription and translation level might provide further insight into the mechanisms eliciting the signal for osmotic stress adaptation in cyanobacteria which might be amenable for application in higher plants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%